Developmental trajectories of the human embryologic brain regions. (24th August 2019) - Oishi, Kumiko; Chotiyanonta, Jill; Wu, Dan; Miller, Michael I.; Mori, Susumu; Oishi, Kenichi; ,
Highlights: The normative growth charts of the human embryologic brain regions were made. The growth trajectories were sex-specific. The growth trajectories were non-linear and region-specific for both sexes. The most active growth was seen in the mesencephalon for both sexes. Abstract: Vertebrate brains commonly consist of five basic embryologic anatomical regions: telencephalon; diencephalon; mesencephalon; metencephalon; and myelencephalon. The proportions of these regions vary widely across species and developmental stages. Investigation of their growth trajectories, therefore, has the potential to provide an understanding of the substrates of inter-species variation in neuroanatomy and function. To investigate the volumetric growth trajectories, structural magnetic resonance imaging (MRI) scans obtained from 618 healthy children (334 boys, 284 girls; ages 3–17 years old) were parcellated into five regions for the volume quantification. The sex- and region-specific growth trajectories were identified, and the most active growth was seen in the mesencephalon for both boys and girls. Whether similar regional growth patterns are seen in other species, or whether such patterns are related to evolution, are important questions that must be elucidated in the future.